A qualitative study of patients' perceptions, interpretations and experiences of fibromyalgia syndrome (FMS) - Namane, Mosedi Keanetse (Department of Public Health and Family Medicine, 2017)
This study was conducted to determine patients' perceptions, interpretations and experiences cf Fibromyalgia syndrome (FMS). Ten patients with FMS attending Heideveld Community Health Centre (CHC) in Cape Town, were selected for their ability to communicate and were interviewed by means of a tape-recorded semi-structured interview conducted at places preferred by the patients. The interviews were transcribed and analysed by detecting common themes. Six themes emerged namely: attitudes of patients towards their illness; perceptions and opinions of patients regarding their illness; patients' descriptions of their symptoms; help-seeking behAviour; consequences of having FMS - mainly loss and fears, hopes and expectations. Another finding was that 5 patients came from dysfunctional families where the dysfunction was found to affect the patient's FMS illness. The interviews brought better understanding of patients' everyday lives and their needs. It became obvious that application of Family Medicine principles to the needs of the patients could improve the quality of care given to them. Also, attention to family functions can help detect patients whose well-being can be improved.